Efficacy and safety of Abelmoschus manihot capsule combined with ACEI/ARB on diabetic kidney disease: a systematic review and meta analysis - Tan, Ying; Zhang, Ziqi; Zhou, Peipei; Zhang, Qiling; Li, Nan; Yan, Qianhua; Huang, Liji; Yu, Jiangyi (Frontiers in Pharmacology, 2024)
Materials and methods: English and Chinese databases such as Pubmed, Cochrane Library, Embase, CNKI, SinoMed, WF, and VIP were searched to collect the RCTs of AM capsule in treatment of DKD. Then Two investigators independently reviewed and extracted data from the RCTs which met the inclusion criteria. The quality of the data was assessed using the Cochrane risk of bias assessment tool, and meta-analysis was performed using RevMan 5.4 software. Results: 32 RCTs with a total of 2,881 DKD patients (1,442 in the treatment group and 1,439 in the control group) were included. The study results showed that AM capsule combined with RASI could be more effective in decreasing 24h-UTP [MD = −442.05, 95% CI (−609.72, −274.38), p＜ 0.00001], UAER [MD = −30.53, 95% CI (−39.10, −21.96), p＜0.00001], UACR [MD = −157.93, 95% CI (−288.60, −27.25), p＜0.00001], Scr [MD = −6.80, 95% CI (−9.85, −3.74), p＜0.0001],and BUN [MD = −0.59, 95% CI (−1.07, −0.12), p=0.01], compared to using RASI alone. According to the subgroup analyses, the combination of AM and ARB seems to be more effective in reducing UAER than the combination of ACEI, and the addition of AM may achieve a more significant clinical effect on decreasing Scr for DKD patients with 24h-UTP ＞ 2g or Scr ＞ 110-133μmol/L and ＞133μmol/L. Furthermore, no additional adverse reactions were observed in the combination group [OR=1.06; 95%CI:(0.66, 1.69), p=0.82]. Conclusions: Combining AM with RASI may be a superior strategy for DKD treatment compared to RASI monotherapy. However, due to significant heterogeneity, the results should be interpreted with great caution, and more high-quality RCTs with multi-centers, different stages of DKD, large sample sizes, and long follow-up periods are still needed to improve the evidence quality of AM for DKD in the future.